PENGARUH KEGIATAN EKSTRAKURIKULER TERHADAP PRESTASI BELAJAR SISWA PADA PESANTREN AL-KHAERAT KOTA GORONTALO - Novianty Djafri (Jurnal Inovasi, 2008)
This research is study about several main problem, that is: (1) extracurricular activity in Pesantren al-Khaerat Gorontalo, (2) learning achievement santri in Pesantren al-Khaerat Gorontalo, (3) extracurricular activity influence which the executed to learning achievement santri. In replying the problems of this research, all of informations is collected with interview and field study. So, the informations have been collected forwardwith percentage at quantitative character. The population is overall of student at Pesantren al-Khaerat Gorontalo namely 121 student. Then amount of students taken as samples in this researches namely 60 people taken away from by student Pesantren al-Khaerat consisting, class I counted 20 people, class II counted 20 people and class III counted 20 people. Added with builder or teacher counted 16 people. From obtained by data-processing result is result that activity of ekstrakurikuler in Pesantren al-Khaerat Gorontalo very effective increased student learning achievement and motivation. But facilities and basic facilities Pesantren al-Khaerat Gorontalo still limited, remember this Pesantren pertained still be new causing require support from all party sides from this continuity of pesantren lives in the future.